Urgensi Penerapan Kepatuhan Syariah pada Perbankan Syariah (Telaah Konseptual-Analitis) - Wulpiah, Wulpiah (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
The issue of shariah compliance is increasingly important, given that Islamic finance is always challenged by demand from market participants to be innovative and business oriented (eg. offering new instruments and products), as conventional financial does. This fact can encourage the Islamic financial position further improve. On the one hand they should accommodate the demand of customers that may be contrary to shariah principles, but on the other hand Islamic banks are strictly bound by shariah compliance. This paper will focus on the importance of applying aspects of shariah compliance in Islamic banking.In various opinions, the meaning of shariah compliance in Islamic banks is “the application of Islamic principles, shariah and traditions in financial transactions and banking and other related business”. Shariah is one of the indicators of Islamic disclosure to ensure the adherence of Islamic banks to shariah principles. Furthermore, at the operational level, shariah compliance is compliance to the Dewan Syariah Nasional which is the embodiment of shariah principles and rules that must be adhered in Islamic banking.Some provisions that can be used to assess shariah compliance within Islamic financial institutions are: First, contract used for the collection and distribution of funds in accordance with the priciples of shariah and the rules of shariah. Second, Zakat funds is calculated and paid, managed in accordance with the rules and principles of shariah. Third, All transactions and economic activities are reported fairy in accordance with applicable shariah accounting standards. Fourth, the work environment and corporate culture in accordance with shariah. Fift, business that are financed do not conflict with shariah. Sixthly, there is Shariah Supervisory Board (DPS) as a shariah director for the overall operational activities of Islamic banks. Seventh, the source of funds comes from a legitimate and lawful source according to shariah.Related to the implementation mechanisme of shariah compliance, there are two underlying concept both in the context of the fulfillment of accuntability horizontally and transcendental. First, The concept of shariah review must be done by DPS to conduct supervision on shariah compliance. Second, the concept of shariah internal review, Islamic banking as one of internal audit function. If the optimazation of the implementation of shariah compliance aspect in Islamic banking is a necessity, so that the impact of Islamic bank can be the only option for the society to save and do the financing.